Broadly Applicable Synthesis of Arylated Dithieno[3, 2‐b:2′, 3′‐d]pyrroles as Building Blocks for Organic Electronic Materials. Issue 48 (29th July 2021) - Vogt, Astrid; Schwer, Fabian; Förtsch, Sebastian; Lorenz, Christoph; Mena‐Osteritz, Elena; Aubele, Anna; Kraus, Teresa; Bäuerle, Peter
Abstract: A novel and versatile method for the N‐arylation of dithieno[3, 2‐ b :2′, 3′‐ d ]pyrrole (DTP) is presented. By Pd‐ or Cu‐catalyzed coupling a variety of arenes and acenes were directly attached at the DTP−nitrogen yielding a variety of functionalized DTPs. Investigations on optical and redox properties led to valuable structure‐property relationships, which were corroborated by quantum chemical calculations. Further functionalization and elongation of the conjugation of an acceptor‐substituted DTP was elaborated to result in complex cruciform‐type donor−acceptor oligomers, which were investigated and implemented in single material organic solar cells. Abstract : A versatile method is presented for the direct N‐arylation of dithieno[3, 2‐ b :2′, 3′‐ d ]pyrrole (DTP) providing a variety of functionalized derivatives. Three catalyst systems were explored, whereby Pd2 dba3 / t Bu3 P showed broad applicability with good yields throughout. Investigations on optical and redox properties led to valuable structure‐property relationships. Further functionalization of an acceptor‐substituted DTP yielded cruciform‐type donor−acceptor oligomers, which were implemented into single material organic solar cells.